The use of hyaluronic acid injection for treatment of black triangle and reconstruction of lost interdental papilla in anterior teeth: a systematic review - Shahad B. Alsharif; Bushra Aljahdali (Medical Journals Sweden, 2024)
Objective: Non-surgical therapeutics to reconstruct lost interdental papilla are evolving; these include hyaluronic acid injection. The aim of this systematic review is to evaluate the efficacy, safety, and long-term outcomes of hyaluronic acid injection in the treatment of black triangles and reconstruction of lost interdental papilla in anterior teeth. Materials and Methods: The protocol was registered in PROSPERO (CRD42023446875) and in accordance with the Cochrane Handbook of Systematic Reviews of Interventions and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis 'PRISMA'. The search involved four databases, PubMed/MEDLINE, The Cochrane Library, Google Scholar, and ProQuest for ''grey literature' with additional manual search for studies published up to May 2024. Human clinical studies of a prospective nature (randomised clinical trials and prospective cohort studies) were included. Exclusion criteria were case reports, case series, review articles, letter to editor, personal opinion, and animal studies. Furthermore, studies which utilised hyaluronic acid injection in conjunction with other therapeutic material, tissue graft, or any surgical procedure were also excluded. The data were extracted independently by the two authors and incorporated after consensus. The risk of bias was assessed using the RoB2: the revised Cochrane risk of bias tool for randomised clinical trials and the Newcastle Ottawa scale for prospective cohort studies. Results: 24 studies, 15 prospective clinical studies and nine randomised clinical trials, were included with a total of 898 interdental papillae injected with hyaluronic acid. The studies showed promising outcomes in the reconstruction of lost interdental papilla with minimal adverse reactions. Risk of bias assessment among prospective clinical studies revealed 13 good quality studies with only two poor studies while the randomised clinical trials consisted of three with low, one with some concern, and five studies with high risk of bias. However, due to the high heterogeneity, a meta-analysis was not feasible.  Conclusion: Hyaluronic acid injection is an effective minimally invasive approach in treating black triangles and reconstructing lost interdental papilla in the anterior teeth. Further long-term well-designed randomised clinical trials employing standardised procedures are essential to validate this treatment and provide better quality of evidence.